Angiogenesis: a curse or cure?. Issue 954 (5th April 2005) - Gupta, K; Zhang, J
Abstract : Angiogenesis, the growth of new blood vessels is essential during fetal development, female reproductive cycle, and tissue repair. In contrast, uncontrolled angiogenesis promotes the neoplastic disease and retinopathies, while inadequate angiogenesis can lead to coronary artery disease. A balance between pro-angiogenic and antiangiogenic growth factors and cytokines tightly controls angiogenesis. Considerable progress has been made in identifying these molecular components to develop angiogenesis based treatments. One of the most specific and critical regulators of angiogenesis is vascular endothelial growth factor (VEGF), which regulates endothelial proliferation, permeability, and survival. Several VEGF based treatments including anti-VEGF and anti-VEGF receptor antibodies/agents are in clinical trials along with several other antiangiogenic treatments. While bevacizumab (anti-VEGF antibody) has been approved for clinical use in colorectal cancer, the side effects of antiangiogenic treatment still remain a challenge. The pros and cons of angiogenesis based treatment are discussed.